PENGARUH PERENDAMAN DALAM CAIRAN RUMEN SAPI TERHADAP PENURUNAN BIOMASSA, DAN PERUBAHAN STRUKTUR ANATOMI KAPAS (GOSSYPIUM SP) - Ika Nur Rakhim Rahayu Setyaningsih; Munifatul Izzati; Teguh Suprihatin (Jurnal Akademika Biologi, 2013)
Energy crisisin many parts ofthe worldencouragesus toseekan alternative solutionto solvethe problem. Sources ofraw materialsin the manufacture ofenergy must beabundant, inexpensive, andeasy toobtain, sotakean ideato useleftovercottoncropswhich containscellulose, as well as usingacowrumen fluidslaughtehousewaste. The purposeof this study toany changesinthe anatomical structure ofcottonfibersand toinvestigate the influence ofbovinerumenfluidtodecreasebiomass.This research was conductedat the Laboratory ofBiologicalStructure and Function ofPlants,Department of Biology, FSM, UNDIP. The design used is descriptive qualitative analysis, and test T. Parameters observed were decreased biomass, and changes in anatomic structure (macroscopic and microscopic). The results showed soaking the cotton in the cow rumen fluid decreased significantly influence cotton biomass, which in the cotton control aerobic larger 0.5% decline from the anaerobic control cotton and cotton anaerobic biomass decreased 3.5% greater than in the aerobic cotton rumen fluid immersion, and anatomical changes in the fiber structure is characterized by significant decomposition of the fiber cell wall. This was done as an initial step in the manufacture of cellulose-based bioethanol. Keywords: immersion, bovine rumen fluid, anatomical structure, cellulose, cotton